2008
DOI: 10.1590/s1516-35982008000600021
|View full text |Cite
|
Sign up to set email alerts
|

Proteína degradável no rúmen na dieta de bovinos: digestibilidades total e parcial dos nutrientes e parâmetros ruminais

Abstract: RESUMO -Quatro novilhos da raça Holandesa (450 kg) portadores de cânula ruminal e duodenal, recebendo dietas com níveis de proteína degradável no rúmen (PDR) de 50, 60, 65 e 70%, associadas a uma fonte de amido de alta degradabilidade ruminal (farinha de varredura de mandioca), foram distribuídos em quadrado latino 4 × 4 para se avaliarem as digestibilidades total e parcial dos nutrientes, a concentração de amônia e o pH ruminal. Foi utilizada, como indicador do fluxo duodenal e fecal, a cinza insolúvel em áci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this situation, the energy supply is usually the first limiting factor of rumen microbial growth (ZEOULA et al, 2003;CALDAS NETO et al, 2008;PINA et al, 2010). The evidence shown in this study corroborate Ezequiel et al (2000), who studied the nitrogen balance and the total digestion of protein and energy from different diets and found that the uniform protein intake made it possible to observe probable differences in the quality of the protein sources utilized.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, the energy supply is usually the first limiting factor of rumen microbial growth (ZEOULA et al, 2003;CALDAS NETO et al, 2008;PINA et al, 2010). The evidence shown in this study corroborate Ezequiel et al (2000), who studied the nitrogen balance and the total digestion of protein and energy from different diets and found that the uniform protein intake made it possible to observe probable differences in the quality of the protein sources utilized.…”
Section: Resultsmentioning
confidence: 99%
“…In general, NB can be positive, negative, or equal to zero (N intake and excretion are more or less the same), which can be used as a metric in assessments of animal health. According to Caldas Neto et al (2008), protein sources of high degradability are generally used more efficiently when associated with easily digestible energy sources, allowing for the synchronization of energy and protein sources and thus improving efficiency in the synthesis of microbial protein that is fixation of the ammoniacal nitrogen present in the rumen.…”
Section: Introductionmentioning
confidence: 99%